Semiologi Komunikasi - Purwasito, Andrik (Mediator, 2006)
There’s no easy way to understand semiology, or semiotics. For sure, semiology is focusing itself to study sign, text, and representation. By employing semiology, scholars try to interpret signs and addressing the politics of representation as reflected on the text. In the field of communication, semiology occupied itself to interpret the meaning which lies behind various means of communication. In order to reveal the hidden meanings behind the text, scholars must equipped themselves with a clear statement of the problem, corpus, scope of problems, and text substance. There are three kind of corpus: (1) primary corpus, e.g. text; (2) comparative orpus; and (3) referent corpus.